Integrasi ESD dalam Pembelajaran dan Penguatan Metodologi Keilmuan Pancasila bagi Guru di Kawasan Bantul Selatan - Lailiy Muthmainnah; Agung Saras Sri Widodo; Hendro Muhaimin (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2016)
Education is key to the process of the formation of character and national identity. Education plays an important role in alleviating poverty, to afrm human rights, eliminate social confict, and reinforce the ideology of the state. Education will also serve as the basis for the realization of sustainable development conditions. Meanwhile the condition of sustainable development can only be achieved by synergizing the various aspects of the life of the state, not only the economic, ecological, social, cultural, but also ideological. Center of Pancasila Studies UGM conducted a series of studies, including research by taking research subjects teachers of Pendidikan Pancasila dan Kewarganegaraan (PPKn) in south Bantul region with the aim of seeing and translating back and reinforcement learning scientifc methodology Pancasila. Tis study intends to map and identify learning models Pancasila has been done by every teacher in the school who will then be summarized into Pancasila model of learning methodologies. Te method of research used the method of focus group discussion (FGD) and training. At the fnal stage of this research can be concluded that the required learning model (methodology) innovative and involve learners in the learning process. Innovative learning process which will arouse the students’ ability to better understand the values that will be the goal of learning. Starting from observing, ask, try, processing, presenting, and concluded. With more innovative learning model, the enthusiasm of the students will be stronger as well as the core values that would be submitted can be understood and implemented by the students.